PENGARUH PERISTIWA KENAIKAN HARGA BBM 18 NOVEMBER 2014 PADA ABNORMAL RETURN SAHAM INDUSTRI TRANSPORTASI DI BEI - Deo Gratias; I Ketut Mustanda (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2015)
The purpose of this study is to determine significant difference on abnormal return of Transportation Industry shares before and after the rise of fuel prices on 18 November 2014.This study took a sample of 24 companies in transportation industry listed on Indonesia Stock Exchange by using cencus method. Data analysis technique used was Paired Sample T-Test with 15-day window period. The results show that there was no significant difference on shares’ abnormal return before and after the rise of fuel price on 18 November 2014. The event of fuel prices hike did not give a significant impact on transportation industry, indicating that the issue of fuel prices hike had been widely circulated within the community before the event occured and it did not take place in a long period of time. It can be stated that the market does not react toward the rise of fuel prices. Investors have predicted that the rise of fuel prices will only be temporary and Indonesia Stock Exchange is still being the destination for foreign investors to invest